2013
DOI: 10.1155/2013/215362
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Study of the Formation of Large-Scale Cyclonic and Anticyclonic Vortices in the Vicinity of the Intertropical Convergence Zone

Abstract: A regional nonhydrostatic mathematical model of the wind system of the lower atmosphere, developed recently in the Polar Geophysical Institute, is utilized to investigate the initial stage of the origin of large-scale vortices at tropical latitudes. The model produces three-dimensional distributions of the atmospheric parameters in the height range from 0 to 15 km over a limited region of the Earth’s surface. Time-dependent modeling is performed for the cases when, at the initial moment, the simulation domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The present study is the continuation of the investigations of the initial stage of the origin of large-scale vortices in the vicinity of an intertropical convergence zone, fulfilled earlier [23] [24]. It is known that an intertropical convergence zone may be considered as a fluid stream, having enhanced zonal velocities, in the ambient atmospheric gas, with a zonal flow of air being westward.…”
Section: Presentation and Discussion Of Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…The present study is the continuation of the investigations of the initial stage of the origin of large-scale vortices in the vicinity of an intertropical convergence zone, fulfilled earlier [23] [24]. It is known that an intertropical convergence zone may be considered as a fluid stream, having enhanced zonal velocities, in the ambient atmospheric gas, with a zonal flow of air being westward.…”
Section: Presentation and Discussion Of Resultsmentioning
confidence: 73%
“…This idea has been confirmed with the help of mathematical modeling [23] [24]. In particular, it was shown that the origin of a convexity in the configuration of the intertropical convergence zone can lead to the formation of a single cyclonic vortex during the period of about one day, with the cyclonic center being close to the southern edge of the initial intertropical convergence zone [23].…”
Section: Presentation and Discussion Of Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…This regional model has been utilized in order to investigate numerically the mechanisms responsible for the formation of large-scale vortices over the ocean surface at tropical latitudes [31][32][33]. In these investigations, it was shown that the origin of convexities in the form of the intertropical convergence zone (ITCZ), having distinct configurations, can lead to the formation of different large-scale vortices, in particular, a 2 Advances in Meteorology cyclonic vortex, pair of cyclonic-anticyclonic vortices, and pair of cyclonic vortices, during the period not longer than three days.…”
Section: Introductionmentioning
confidence: 99%